Redefining the global populations of Pseudomonas syringae pv. actinidiae based on pathogenic, molecular and phenotypic characteristics. (26th May 2014) - Ferrante, P.; Scortichini, M.
<x xml:space="preserve">Abstract</x> Knowing the population structure of a pathogen is fundamental for developing reliable phytosanitary legislation, detection techniques, and control strategies based on the actual aggressiveness and distribution of the pathogen. Currently, four populations of Pseudomonas syringae pv. actinidiae (Psa) have been described: Psa 1, Psa 2, Psa 3 and Psa 4. However, diagnostic assays specific for Psa populations do not detect Psa 4, the less virulent (LV) strains isolated in New Zealand. Similarly, multilocus sequence typing (MLST) of housekeeping genes, or broad Psa strain genome comparisons, revealed that Psa 4‐LV strains clustered separately from other Psa populations. In order to examine whether the placement of Psa 4 in the pathovar actinidiae was appropriate, various tests were carried out. It was shown that the Psa 4‐LV strains induced leaf and shoot wilting in Prunus cerasus, extensive necrotic lesions in Capsicum annuum fruits, and no significant symptoms in Actinidia deliciosa. Moreover, repetitive‐sequence PCR fingerprinting, type III secretion system effector protein genes detection and colony morphology clearly indicated the distinctiveness of Psa 4‐LV strains from the other three Psa populations. Rep‐PCR molecular typing revealed a high similarity of the Psa 4‐LV strains with members of Pseudomonas avellanae species. The Psa 4‐LV strains, most probably, belong to a new, still unnamed pathovar. It was concluded that the Psa 4‐LV strains isolated in New Zealand do not belong to the pathovar actinidiae, and, consequently, three Psa populations pathogenic to Actinidia spp. should currently include Psa 1, Psa 2 and Psa 3.